Preventing derailment : what to do before it's too late - Lombardo, Michael M. (Technical report (Center for Creative Leadership) ;, 1989)
Some of the strengths that lead high-potential managers to early promotions can become weaknesses. When this happens, many whose careers have been full of promise stumble, creating huge organizational and personal waste. Much derailment, however, is preventable. By looking at the problem from both an individual and organizational perspective, this report shows how.